Early clinical management of severe burn patients using telemedicine: a pilot study protocol - Maxim Moreau (Pilot and Feasibility Studies, 2020)
Abstract Background Emergency physicians are responsible for assessing the severity of a patient’s burns, which determines whether the patient needs to be transferred to a burn center. Such a proper assessment represents a daunting task because severe burn injuries are rare. Inaccurate estimates often result in unjustified and costly transfers and unneeded fluid resuscitation and assisted ventilation procedures. Telemedicine offers a solution to these challenges. The present pilot study aims to investigate the feasibility, acceptability, and potential value of a large telemedicine initiative at the University of Montreal Health Center’s burn center and its network of referring hospitals. Methods A three-stage study protocol is proposed to achieve this objective. First, a proof of concept phase will assess the technical feasibility of telemedicine at one referring hospital with a high volume of patient transfers. Second, the organizational and human feasibility of the project will be evaluated in four referring medical centers. All teleconsultation sessions will be analyzed using the WHO’s telemedicine implementation model. The third phase will consist of evaluating the potential impacts of telemedicine in a subset of 10 referring hospitals. The quality of communications between referring physicians and specialists will be assessed using semi-structured interviews. A pre-test/post-test with a comparison group design will be used to assess the effects of telemedicine on patient transfers, ventilation procedures, patient complications, mortality, length of ICU stay, and additional surgical procedures. The economic viability of telemedicine will be assessed using a cost-minimization approach. Discussion The telemedicine initiative is expected to yield positive and significant outcomes that are relevant to a wide range of medical centers that already use or are considering using a similar technology. The contribution of this pilot study lies in its ability to reveal technological, organizational, and human barriers and provide a preliminary assessment of the clinical and economic value of a large-scale telemedicine initiative in the context of burn medicine.